2010
DOI: 10.1016/j.bpj.2009.12.4280
|View full text |Cite
|
Sign up to set email alerts
|

Alternans Resonance and Propagation Block during Supernormal Conduction in Cardiac Tissue with Decreased [K+]o

Abstract: Cardiac restitution is an important factor in arrhythmogenesis. Steep positive action potential duration and conduction velocity (CV) restitution slopes promote alternans and reentrant arrhythmias. We examined the consequences of supernormal conduction (characterized by a negative CV restitution slope) on patterns of conduction and alternans in strands of Luo-Rudy model cells and in cultured cardiac cell strands. Interbeat intervals (IBIs) were analyzed as a function of distance during S1S2 protocols and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Our results are highly relevant to excitable media and to all experiments where SNC is found in cardiac tissue (see, e.g., Ref. [13]). With respect to alternans, the experimental observation of straight defect lines in period-doubled spirals in cell cultures of cardiac rat cells [21] …”
supporting
confidence: 58%
See 2 more Smart Citations
“…Our results are highly relevant to excitable media and to all experiments where SNC is found in cardiac tissue (see, e.g., Ref. [13]). With respect to alternans, the experimental observation of straight defect lines in period-doubled spirals in cell cultures of cardiac rat cells [21] …”
supporting
confidence: 58%
“…SNC is found, for example, in the Iyer-Mazhari-Winslow [9] or in the Drouhard-RobergeBeeler-Reuter (DRBR) model [10,11] employed in the study here, and it is often observed under conditions of low extracellular potassium concentration [12]. Recently, it has been shown to potentiate the onset of alternans in cultured cardiac cell strands [13] and also in generic models of spiral wave formation [14].Alternans is an oscillation in the duration of the AP that usually occurs at short stimulation periods [15]. In a paced cable or tissue alternans appears in two major forms, concordant (CA) and discordant (DA) alternans, depending on if the phase of the alternation is the same along the tissue or it presents nodes (in 1D) or nodal lines (in 2D) separating regions of tissue oscillating out of phase.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…It has been shown that abnormal CV restitution can cause alternans and initiation of spiral waves [49], [50], and also important phenomena on spiral wave dynamics such as discordant alternans can be caused by abnormal CV restitution [51], [52]. We expect that this mechanism of mechanically caused abnormal CV-restitution is important to understand the onset of arrhythmias due to emergent dynamic inhomogeneities.…”
Section: Discussionmentioning
confidence: 93%
“…This initial increase was attributed to supernormal conduction, whereby the initial slight depolarization by a low number of MFBs brings the RMP of CMCs closer to the threshold of I Na activation (thus accelerating conduction), whereas further RMP depolarization causes partial I Na inactivation (thus slowing conduction). While our CMC model (based on Luo-Rudy I Na dynamics) can reproduce supernormal conduction caused, e.g., by a change of [ K + ] o (Luo and Rudy, 1991; de Lange and Kucera, 2009, 2010), it failed to reproduce supernormal conduction caused in experiments by a small density of MFBs (Miragoli et al, 2006). This observation is not surprising, since our model is characterized by a high coupling regime (see above).…”
Section: Discussionmentioning
confidence: 88%